1988
DOI: 10.1128/aem.54.4.937-944.1988
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of phenanthrene by a Mycobacterium sp

Abstract: A Mycobacterium sp., designated strain BG1, able to utilize the polycyclic aromatic hydrocarbon phenanthrene as the sole carbon and energy source was isolated from estuarine sediment following enrichment with the hydrocarbon. Unlike other phenanthrene degraders, this bacterium degraded phenanthrene via 1-hydroxy-2-naphthoic acid without accumulating this or other aromatic intermediates, as shown by high-performance liquid chromatography. Degradation proceeded via meta cleavage of protocatechuic acid. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
8

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(77 citation statements)
references
References 42 publications
2
67
0
8
Order By: Relevance
“…A number of investigators have demonstrated that surfactants can enhance bioavailability of PAHs by increasing rates of their mass transfer (e.g., dissolution or desorption) to the aqueous phase in which microbial uptake occurs [2][3][4][5], or micelle-associated PAHs are directly available to PAH-degrading microbes via direct contact between micelles and microbes [6,7]. The extent of stimulation varies with the type and concentration of surfactants and the type of microorganisms involved [8][9][10][11][12][13]. Conversely, others have reported surfactant additions to inhibit, or at least not enhance, PAH biodegradation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have demonstrated that surfactants can enhance bioavailability of PAHs by increasing rates of their mass transfer (e.g., dissolution or desorption) to the aqueous phase in which microbial uptake occurs [2][3][4][5], or micelle-associated PAHs are directly available to PAH-degrading microbes via direct contact between micelles and microbes [6,7]. The extent of stimulation varies with the type and concentration of surfactants and the type of microorganisms involved [8][9][10][11][12][13]. Conversely, others have reported surfactant additions to inhibit, or at least not enhance, PAH biodegradation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Guerin and Jones [16] evaluated the effect of several Tween surfactants on the bacterial utilization of polycyclic aromatic hydrocarbons and found Tween-60 to be more successful in enhancing the growth of a Mycobacterium sp. on phenanthrene than Tween-85, -80, -40, or -20 (listed in order of decreasing rate of phenanthrene utilization).…”
Section: Discussionmentioning
confidence: 99%
“…However, Tween-80 may not be the most ideal surfactant for use in biological systems. Reports in the literature [8,16] and preliminary testing in our laboratory (unpublished data) have indicated instances in which Tween-80 was less successful in promoting the biotransformation of HOCs compared with other members of the Tween series. Consequently, all Tween surfactants need to be examined individually to assess the effect of their structural differences on biological processes to identify the most favorable Tween surfactants for use in bioavailability applications.…”
Section: Introductionmentioning
confidence: 91%
“…Two other studies, using a series of Tweens with HLB values between 10 and 17, observed maximum degradation of phenanthrene [13] and alkanes [11] with addition of the more lipophilic surfactant, Tween 85 (HLB ϭ 11). Assuming that the rate of hydrocarbon dissolution limited bioavailability, the authors suggested that the lower cmc of the more lipophilic surfactants resulted in increased interfacial area, enhancing hydrocarbon utilization.…”
Section: Interactions Of Surfactants With Microbial Membranesmentioning
confidence: 96%
“…Most studies that have examined surfactant effects on microbial HOC degradation have looked at hydrocarbon utilization by pure cultures in aqueous media. Several of these studies, using a variety of nonionic surfactants, demonstrated a positive effect on microbial growth concurrent with enhanced degradation of hydrocarbon substrate [1,2,5,[11][12][13][14][15]. Generally, no evidence of surfactant degradation was observed.…”
Section: Introductionmentioning
confidence: 99%